2014
DOI: 10.1039/c4ra06027j
|View full text |Cite
|
Sign up to set email alerts
|

An efficient catalyst-free and chemoselective synthesis of azobenzenes from nitrobenzenes

Abstract: NaOH mediated reaction of nitrobenzenes in EtOH was performed at 80 C temperature affording azobenzenes in excellent yield. This methodology presents an easy synthesis of a wide variety of azo compounds from readily available nitrobenzene derivatives.a II-aniline, III-azoxybenzene, IV-azobenzene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…A recent study has demonstrated that selective photosynthesis of azobenzene can also be realised at elevated temperature (90 °C), by using a cheaper metal (Cu) supported on graphene (Table 1 , entry 3) 17 , 20 . However, since the nitrobenzene reduction can be initiated at 80 °C without any catalyst (poor activity and selectivity) 21 , the use of an expensive graphene support in a reaction that is inefficient at RT, affects its commercial potential negatively. In addition, the supported plasmonic metal nanoparticle based photocatalysts (i.e., Au, Ag, and Cu) show a relatively poor efficiency for light absorption compared to their semiconductor counterpart, and the particle size of the metal would have to be controlled strictly to absorb photons with the desired energies 25 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has demonstrated that selective photosynthesis of azobenzene can also be realised at elevated temperature (90 °C), by using a cheaper metal (Cu) supported on graphene (Table 1 , entry 3) 17 , 20 . However, since the nitrobenzene reduction can be initiated at 80 °C without any catalyst (poor activity and selectivity) 21 , the use of an expensive graphene support in a reaction that is inefficient at RT, affects its commercial potential negatively. In addition, the supported plasmonic metal nanoparticle based photocatalysts (i.e., Au, Ag, and Cu) show a relatively poor efficiency for light absorption compared to their semiconductor counterpart, and the particle size of the metal would have to be controlled strictly to absorb photons with the desired energies 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Fig 5 exhibits possible mechanistic pathways for transetherification, which could account for ortho -selectivity and high conversion of para -methoxy and para -diethylamino substrates to 2 . With regard to the formation of byproduct 3 , nitrobenzene could be reduced to aniline in the presence of alcohol and base [ 23 ]. A small amount of nitrobenzene may be reduced to aniline in the presence of methoxide released from substrate at high temperature, which may quickly react with substrate 1 to give byproduct 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The use of 10% dimethoxyethane (DME) increased the formation of the desired product 2 and reduced that of 3 (Table , entry 2), compared to the condition without DME (Table , entry 1). DME may impede the reduction of the nitrobenzene to aniline through interaction with the nitro group, assuming its role based on the reports that nitrobenzenes could be reduced to anilines or azobenzenes in the presence of alkoxide . Our interest has been concentrated on additives as alternatives of DME that affect the S N Ar reaction.…”
Section: Effect Of Additives On Nucleophilic Substitutionmentioning
confidence: 99%
“…DME may impede the reduction of the nitrobenzene to aniline through interaction with the nitro group, assuming its role based on the reports that nitrobenzenes could be reduced to anilines or azobenzenes in the presence of alkoxide. 12,13 Our interest has been concentrated on additives as alternatives of DME that affect the S N Ar reaction. Herein, we describe the additives affecting the S N Ar reaction of 2,4-dimethoxynitrobenzene with sodium tertbutoxide.…”
mentioning
confidence: 99%